معوقات البحث العلمي الجامعي في الجزائر - بن عودة، نصر الدين Bin Oudah, Nasr Uldin; مقداد، علي (مؤسسة كنوز الحكمة للنشر والتوزيع, 2018)
يعتبر البحث العملي نشاطا أساسيا في المنظومة الجامعية، إذ تحاول الجامعة الجزائرية الاهتمام بمجال التعليم العالي والاستثمار فيه، ورغم المجهودات المعتبرة التي بذلتها الدولة من أجل هيكلة وتطوير البحث العلمي في الجامعة، إلا أن حدود مساهمتها تظل متدنية، هذا ما دفعنا نتسائل عن العوائق التي تحول دون زيادة اهتمامها وتمويلها في مجال إنتاج المعرفة العلمية، ومن ثم عدم استخدامها الفعلي في مجال التنمية وتحسين الواقع الاقتصادي، وهذا ما جعلنا نطرح التساؤل التالي: ما هي معيقات البحث الجامعي في الجزائر؟
The scientific research is considered such as a principal activity in the academic organization, however the Algérian university tries to give interest to the higher education’s field and to invest in it , despite the considerable efforts made by the nation to develop the scientific research at the university ,its contribution’s conditions remain weak, that what incites us to ask questions about the impediments to increase its interest to scientific knowledge’s field and its financing ,and then its real non use in the development’s area and the improvement of the economic reality. That is what incites us to ask the following question: What are the handicaps of the development of the scientific research in the Algerian university?
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- البحوث العلمية -- التعليم الجامعي -- طلاب الجامعات -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث